Hubungan Mental Toughness dan Competitive Anxiety terhadap Peak Performance Atlet Basket Sumbar - Yusuf, Lustyana; Aulia, Prima (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
Correlation Mental Toughness and Competitive Anxiety to peak performance basketball atheletes Sumbar.This research aims to determine the relationship between mental toughness and competitive anxiety on peak performance in basketball athletes in West Sumatra. In this reseacrh usedthequantitavivecorrelation. This research used a sample quota technique in sampling. Population in this research were basketball athletes based in West Sumatra with 27 subjects. Theresulthasacorrelationof0.790 witha valuep =0,000(pË‚0,05), it means The higher the mental toughness of an athlete, the lower the competitive anxiety in an athlete and the effect on the peak performance of an athlete will be higher, the opposite is also true